Assessment of Knowledge and Opinions of Family Medicine Residents About the Diagnosis and Treatment of Enuresis in Children - Seçil Arslansoyu Çamlar; Esma Uysal; Eren Soyaltın; Gökçen Erfidan; Demet Alaygut; Fatma Mutlubaş; Hülya Parıldar; Belde Kasap Demir (Journal of Pediatric Research, 2021)

(untitled)
Aim:Enuresis (EN) is a common problem in childhood. Family physicians have an important role in revealing children with EN. The aim of this study was to assess the knowledge and attitude of family medicine (FM) residents regarding the diagnosis and treatment of enuresis in children.Materials and Methods:Family medicine residents of the University of Health Sciences, İzmir Tepecik Training and Research Hospital were invited to complete a questionnaire concerning enuresis in children. Those who had completed their paediatrics rotation training were defined as group 1, and those who had not completed their paediatrics rotation as group 2. The responses were compared between the groups.Results:Sixty (88%) of the FM residents agreed to complete the survey. The mean age of the participants was 28.7 (25-35) years, 38 (63%) had completed their paediatrics rotation (group 1). The question about the age of night-time bedwetting was more often answered correctly in group 1 (19/38) (p=0.025). In the question on the symptoms of non-monosymptomatic enuresis; the constipation option was marked as a symptom by only 15 of the participants (25%), with 13 (87%) being in group 1 (p=0.03). The correct response rates to the questions about other symptoms of non-monosymptomatic enuresis, the causes of secondary enuresis, the need for treatment, treatment options and the follow-up of patients with enuresis were similar between groups 1 and 2.Conclusion:As a result of this study, more correct answers, which revealed adequate knowledge and experience regarding enuresis, were obtained from those who had concluded their paediatrics rotation.